"Academic Redshirting" in Kindergarten: Prevalence, Patterns, and Implications. (September 2013) - Bassok, Daphna; Reardon, Sean F.
We use two nationally representative data sets to estimate the prevalence of kindergarten "redshirting"—the decision to delay a child's school entry. We find that between 4% and 5.5% of children delay kindergarten, a lower number than typically reported in popular and academic accounts. Male, White, and high-SES children are most likely to delay kindergarten, and schools serving larger proportions of White and high-income children have far higher rates of delayed entry. We find no evidence that children with lower cognitive or social abilities at age 4 are more likely to redshirt, suggesting parents' decisions to delay entry may be driven by concerns about children's relative position within a kindergarten cohort. Implications for policy are discussed.